2013
DOI: 10.1111/dsu.12246
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography Imaging in the Management of Merkel Cell Carcinoma: A Single-Institution Retrospective Study

Abstract: Fluorodeoxyglucose-positron emission tomography and computed tomography is a valuable tool for initial staging and to assess response to therapy of patients diagnosed with MCC. Larger prospective studies would be required to establish the optimal timing for this imaging modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…They may be performed during the initial staging of the patient when distant metastases are suspected or when a cutaneous metastasis from a noncutaneous primary neuroendocrine carcinoma is considered [7, 10, 11]. Our patient had a history of multiple lipomas and presented with metastatic Merkel cell carcinoma to his left inguinal lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…They may be performed during the initial staging of the patient when distant metastases are suspected or when a cutaneous metastasis from a noncutaneous primary neuroendocrine carcinoma is considered [7, 10, 11]. Our patient had a history of multiple lipomas and presented with metastatic Merkel cell carcinoma to his left inguinal lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Siva et al showed that FDG played a very important role in the risk stratification and management of MCC patients [32]. In their large series involving prospective analysis of 102 patients, they observed that PET changed the management plan in 37% of patients which was in parallel with prior studies in smaller series and somewhat more than 15% reported by Ibrahim et al [31]. They also showed that presence of nodal disease on PET and the presence of any metabolically active disease on PET were associated with decreased overall and progression free survival.…”
Section: Molecular Imaging and Therapy Of Merkel Cell Carcinomamentioning
confidence: 56%
“…In one report comprising 21 patients, FDG results changed staging in 33% of the patients with MCC and altered management in 43% of the patients [28]. Hawryluk et al retrospectively reviewed 270 FDG PET/CT studies performed in 97 patients and concluded that FDG resulted in upstaging in 16% of patients [30] similarly a retrospective single center study reported changes in tumor status in 20% of patients [31]. Recently, Siva et al showed that FDG played a very important role in the risk stratification and management of MCC patients [32].…”
Section: Molecular Imaging and Therapy Of Merkel Cell Carcinomamentioning
confidence: 99%
“…In another retrospective study of 15 MCC patients, Maury and colleagues showed no change to staging after FDG PET‐CT in all five SLNB‐negative (stage IA) and two SLNB‐positive (stage IIIA) patients . Ibrahim and colleagues demonstrated similar results in eight stage I patients (one stage IA, seven stage IB) in a single institution retrospective study …”
Section: Discussionmentioning
confidence: 86%